The investigation of possible use of unmarketable cracked eggs in lamb milk replacer - Guler, T.; Ciftci, M.; Ertas, O. N.; Cerci, I. H.; Dalkilic, B. (Ecole Nationale Veterinaire Toulouse, 2006)
This study was conducted to determine the possible use of unmarketable cracked eggs (UCE) in milk replacer. Twenty lambs, approximately 3 d old. were used in a randomly allocated to two groups each consisting of 10 lambs. First group was fed with milk, as liquid feed (Milk group) and the other group was fed with lamb milk replacer (LMR) as liquid feed (LMR group). Alfalfa hay and concentrate feed were given ad libitum. The effect of each ration was investigated with regard to the feed intake, body weight gain and feed efficiency in lambs. Among the trial period (1-56(th) d) daily feed intake in milk and LMR groups was found for hay average 99.83 g and 93.75 g (p>0.05), for concentrate average 327.99 g and 314.79 g. respectively (p>0.05). Liquid feed (milk and LMR) were given average 500 ml/d in to the both groups during the 1-56(th) d. Daily body weight (BW) gain and feed conversion ratio in Milk and LMR groups were 248.75 g and 244.28 g (p>0.05), 2.08 and 2.02 (p>0.05), respectively. To be result of, we opinion. unmarketable eggs may be use for suckling lambs feeding and the proteins of LMR approximately 58% will be able to providing from UCE.
Keywords: milk; milk replacer; cracked egg; performance; lamb